Environmental Literacy and Care Behavior Through Adiwiyata Program at Elementary School - Sunarto Sunarto (STAI Hubbulwathan Duri, 2023)
The dissemination of educational behaviours that enhance students' environmental literacy should be prioritised in light of the escalating environmental degradation. This research aims to: (1) describe the implementation of Adiwiyata program activities; (2) describe the environmental literacy skills; (3) describe the environmental care attitude; and (4) identify the factors that support or impede the implementation of adiwiyata program at a private elementary school in Bogor Regency. The qualitative descriptive study was done at a provincial-level Adiwiyata school from September 2021 to January 2022, employing qualitative descriptive methodologies. Written tests containing questions and questionnaires, interviews with instructors and students, observations, and documentation were utilized to disseminate data collection techniques. The assessment of environmental literacy is based on three indicators: (1) ecological knowledge, (2) environmental affection, and (3) behaviors. According to the findings of this study, this elementary school employs eco-friendly practices in order to attain Adiwiyata. The results of this study indicate that each indicator received a score of 75, 39.15, and 19.6 for the favorable category. The attitude of concern for the environment received a score of 76.42 in the category of excellence. These results are influenced by (1) quality environmental education, (2) student participation in environmental activities, and (3) student environmental knowledge. There are obstacles to the implementation of Adiwiyata, such as a lack of interest from school residents, an uneven distribution of environmental care, and the expense of carrying out activities. This study's findings will serve as an evaluation tool for the school's efforts to maximize Adiwiyata activities.